2019
DOI: 10.1590/1678-4324-2019180715
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of C-repeat Binding Factors (CBFs) in Tomato and Arabidopsis

Abstract: Cold stress is one of the limiting factors of plant production that plants use different mechanisms for cold tolerance. CBF genes play critical role to regulate the cold responsive genes. To better understand of CBF gene functions, the tomato-CBFs and Arabidopsis-CBFs were evaluated using bioinformatics tools, and finally the expression patterns of SlCBF1 gene were analyzed under 10 and 4˚C in two contrasting tomato species (Solanum lycopersicum and S. habrochaites). The different cis regulatory elements were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Previous studies have also illustrated that the genes encoding DREB proteins are significantly cold and drought responsive, so overexpression of these genes could improve drought, salt, and cold tolerance in plants [19,81,95]. Furthermore, DRE is a core sequence of genes involved in the response to drought and cold stresses [3,18,96]. A DREB2 homolog Wdreb2 gene, which was firstly isolated from bread wheat, is activated by abiotic stresses such as salt, drought, cold, and exogenous ABA application [97].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also illustrated that the genes encoding DREB proteins are significantly cold and drought responsive, so overexpression of these genes could improve drought, salt, and cold tolerance in plants [19,81,95]. Furthermore, DRE is a core sequence of genes involved in the response to drought and cold stresses [3,18,96]. A DREB2 homolog Wdreb2 gene, which was firstly isolated from bread wheat, is activated by abiotic stresses such as salt, drought, cold, and exogenous ABA application [97].…”
Section: Discussionmentioning
confidence: 99%
“…The DREB proteins encoding genes are significantly responsive to drought and cold, so overexpression of these genes in plants could increase salt, drought, and cold tolerance ( Shigyo et al, 2006 ; Lata et al, 2014 ; Shu et al, 2016 ). Additionally, DRE is the central sequence of those genes that are involved in cold and drought stress-responsive ( Lata and Prasad, 2011 ; Heidari, 2019 ; Xu et al, 2020 ). In this study, we identified different types of cis -acting elements like growth and development, CAT-box involved in meristem expression, Box-4, and MRE play role in light responsiveness, and O2-site essentially functions in zein metabolism regulation.…”
Section: Discussionmentioning
confidence: 99%
“…These results revealed that tomato SAMS genes have tissue-specific expression patterns. Tissue-specific expression can provide insight into the different functions of target genes in different organs [50,51]. The qRT-PCR results revealed that Solyc01g101060 and Solyc09g008280 were downregulated under heat stress and water stress and that the expression of the Solyc10g083970 gene was downregulated under all abiotic stresses and hormone treatments (Figure 8).…”
Section: Discussionmentioning
confidence: 99%